2017
DOI: 10.1016/j.nicl.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional connectivity is associated with visceral sensitivity in women with Irritable Bowel Syndrome

Abstract: Increased perception of visceral stimuli is a key feature of Irritable Bowel Syndrome (IBS). While altered resting-state functional connectivity (rsFC) has been also reported in IBS, the relationship between visceral hypersensitivity and aberrant rsFC is unknown. We therefore assessed rsFC within the salience, sensorimotor and default mode networks in patients with and without visceral hypersensitivity and in healthy controls (HCs).An exploratory resting-state functional magnetic resonance imaging study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 71 publications
(97 reference statements)
5
67
0
4
Order By: Relevance
“…Female patients with IBS showed an upregulation of emotional arousal circuits during an aversive rectal stimulus, and greater emotional arousal circuit activation was found during expectation of the rectal stimulus . Female patients with IBS also showed alterations in intrinsic oscillation in the INS and its functional connectivity . Like IBS and many other FGID, FC is more prevalence in women with a mean female to male ratio of 2.1:1 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Female patients with IBS showed an upregulation of emotional arousal circuits during an aversive rectal stimulus, and greater emotional arousal circuit activation was found during expectation of the rectal stimulus . Female patients with IBS also showed alterations in intrinsic oscillation in the INS and its functional connectivity . Like IBS and many other FGID, FC is more prevalence in women with a mean female to male ratio of 2.1:1 .…”
Section: Introductionmentioning
confidence: 95%
“…15 Female patients with IBS also showed alterations in intrinsic oscillation in the INS 8 and its functional connectivity. 16,17 Like IBS and many other FGID, FC is more prevalence in women with a mean female to male ratio of 2.1:1. 18,19 To the best of our knowledge, only one resting-state fMRI (RS-fMRI) study from our group has been performed in patients with FC and revealing brain abnormalities in regions implicated in emotional process modulation, somatic and sensory processing, and motor control.…”
Section: Introductionmentioning
confidence: 99%
“…Icenhour et al 63 reported that resting-state functional connectivity value in the default mode network (DMN) (Fig. 3B) and the sensorimotor network was associated with rectal perception thresholds, and that the resting-state functional connectivity value in the posterior insula was correlated with the reported symptom severity in IBS.…”
Section: Independent Component Analysismentioning
confidence: 99%
“…Since our study is cross-sectional, the signs of cardiovascular autonomic dysfunction in patients with severe functional GI symptoms may be primary or secondary to the GI disease, with several possible explanations. First, autonomic neuropathy secondary to GI symptoms may be an effect of the peripheral and/or central hypersensitization associated with functional GI disorders [3], with aggravated ANS responses, due to afferent signals from the GI tract being dispersed to amygdala, hippocampus, insula, cingulate cortex and other brain centers modulating pain signals [5,29]. Second, a primary autonomic dysfunction such as present in genetic diseases [16], Parkinson's disease [10] or diabetes mellitus [9], may act as a causal agent disturbing both afferent and efferent pathways between the gut and brain.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent manifestation of FGID is irritable bowel syndrome (IBS) [1]. It has been demonstrated that IBS is strongly related to stress, psychological disorders [2] and visceral hypersensitivity [3]. The enteric nervous system (ENS) is a part of the autonomic nervous system (ANS), which constitutes the anatomical and physiological basis for correlations between visceral hypersensitization and autonomic dysfunction [4].…”
Section: Introductionmentioning
confidence: 99%